Kondisi Sosial Ekonomi Petani Nilam Di Desa Tambarana Kecamatan Poso Pesisir Utara Provinsi Sulawesi Tengah - Indriawati, Novia; Mandei, Juliana Ruth; Jocom, Sherly Gladys (AGRI-SOSIOEKONOMI, 2023)
This study aims to determine how the socio-economic conditions of patchouli farmers in Tambarana Village, Poso Pesisir Utara District, Central Sulawesi Province. This research was conducted from October to December 2021. The data used in this study consisted of primary data and secondary data. Primary data was obtained through direct interviews with 43 respondents using a questionnaire and secondary data obtained from the Tambarana Village government office, literature or previous research. The sampling method was carried out by means of a cluster (cluster random sampling). The method of data analysis is descriptive qualitative and quantitative analysis The results showed that the social conditions of patchouli farmers had a good interaction relationship between farmers, doing mutual cooperation, in terms of education many farmers' children can continue their education to a higher level, the health level is also improving, many people have taken treatment to the puskesmas/doctor, while the economic condition of patchouli farmers due to an increase in income with an average of Rp. 3.961.604/month for farmers, the educational level of many of the farmers' children continue to higher education, health conditions are improving, they have houses made of concrete with zinc roofs and slab floors, farmers have the most number of dependents in the family, namely 1-4 people. Rubber farmers' land area <0.5 Ha with a production level of 15 – 26 Kg, in general, the income of farmers after patchouli farming, but there are also farmers who earn other than patchouli farming, there are also farmers who have other jobs such as breeders. Buying and selling fish, laborers, honorary workers, civil servants, village heads, and cooperative employees.